Secondary metabolites from the Endophytic fungi Fusarium decemcellulare F25 and their antifungal activities - Song, Ziwei; Sun, Yan Jun; Xu, Shuangyu; Li, Gang; Yuan, Chunmao; Zhou, Kang (Frontiers in Microbiology, 2023)
Seven new compounds, including three isocoumarins (1–3), three pyrrolidinone derivatives (8–10), and one pentaene diacid (15), together with thirteen known compounds, were isolated from the rice culture of the endophytic fungus Fusarium decemcellulare F25. Their structures and stereochemistry were established by extensive spectroscopic analyses including HRESIMS, NMR, electronic circular dichroism (ECD) calculations, and single-crystal X-ray diffraction. The possible biosynthetic pathways for compounds 1–3 and 8–10 were proposed. The antifungal efficacies of compounds 1 ̶ 20 were evaluated against Colletotrichum musae, and compounds 13, 14, and 17 exhibited inhibitory activities against C. musae with MIC values of 256, 64 and 128 μg/mL, respectively.